2020
DOI: 10.1111/liv.14629
|View full text |Cite
|
Sign up to set email alerts
|

LncRNANEAT1: Shedding light on mechanisms and opportunities in liver diseases

Abstract: With advances in genome and transcriptome research technology, the function and mechanism of lncRNAs in physiological and pathological states have been gradually revealed. Nuclear Enriched Abundant Transcript 1 (NEAT1, a long non-coding RNA), a vital component of paraspeckles, plays an indispensable role in the formation and integrity of paraspeckles. Throughout the research history, NEAT1 is mostly aberrantly upregulated in various cancers, and high expression of NEAT1 often contributes to poor prognosis of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 122 publications
0
41
0
1
Order By: Relevance
“…Liu et al [ 62 ] reported that BMMSCs transfected with ANGPT1 had therapeutic effects on hyperoxia induced optic nerve injury. With respect to non-coding RNAs in the networks, NEAT1 has been proven to act as an oncogene in multiple cancers by binding to various miRNAs [ 63 , 64 ]. LINC02595 could promote colorectal cancer progression by inhibiting miR-203b-3p activity [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 62 ] reported that BMMSCs transfected with ANGPT1 had therapeutic effects on hyperoxia induced optic nerve injury. With respect to non-coding RNAs in the networks, NEAT1 has been proven to act as an oncogene in multiple cancers by binding to various miRNAs [ 63 , 64 ]. LINC02595 could promote colorectal cancer progression by inhibiting miR-203b-3p activity [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the networks between lncRNAs and miRNAs performed important regulatory roles in the pathogenesis of various human cancers and fibrotic diseases [ 31 ]. Among quantities of lncRNAs relevant to fibrogenesis, NEAT1 is a lncRNA originally serving as mammary development regulator, which was later verified to be intimately associated with fibrotic diseases [ 32 ]. Although NEAT1 was shown to regulate liver fibrosis and HSCs activation, the specific signaling pathways mediating its roles in liver fibrosis remain poorly known.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al and colleagues [56] also illuminated that BMMSCs transfected with ANGPT1 had therapeutic effects on hyperoxia induced optic nerve injury. As for non-coding RNAs in the networks, NEAT1 have been proven to act as an oncogene in multiple cancers via binding various miRNAs [57,58]. LINC02595 could promote colorectal cancer progression by inhibiting miR-203b-3p…”
Section: Discussionmentioning
confidence: 99%